Ascension - Golden, Christie (Star wars, fate of the Jedi., 2012)
As Luke and Ben Skywalker pursue the formidable dark-side, the Lost Tribe of the Sith is about to be sundered by an even greater power--which will thrust one dark lord into mortal conflict with his own flesh and blood.